Incentives for industry in developing countries - Heinz Ludwig (Intereconomics, 1976)
In support of their industrialisation efforts developing countries are offering a number of incentives to investors in order to compensate the latter for shortcomings and handicaps resulting from the countries' development status. Do these incentives serve their purpose?
Keywords: 330; Industrialisation